Eksplorasi Fungsi Tindak Tutur Komisif sebagai Konsep Bushido pada Tokoh Samurai dalam Film Rurouni Kenshin - Safitri, Dian Eka; Situmorang, Hamzon; Hasibuan, Namsyah Hot (Journal of Japanese Language Education and Linguistics, 2020)
This research aims to know the functions of commissive speech acts spoken by samurai characters in Rurouni Kenshin film and its relation to the concept of bushido. In collecting data, the researchers used the refer method by download technique, continued by note technique. In analyzing data, noted speech acts classified by its functions using the padan method by the determinant of the speech partner, then adapted to the concept of bushido. Based on the result, there were 17 commissive illocutionary speech acts of samurai characters in the Rurouni Kenshin film. The functions found were promising (4 speeches), threatening (8 speeches), refusing (1 speech), offering (3 speeches), guaranteeing (1 speech). Based on the bushido concept, 1 speech of honor value (meiyo), 2 speeches of virtue value (jin), 1 speech of sincerity value (gi), 3 speeches of courage value (yuu), 2 speeches of loyalty value (chuugi), 1 speech of honesty value (makoto), 0 speech of politeness value, and 7 speeches which not following the concept of bushido. In 1868-1878, the bushido concept still used, although some speech acts were not developing the bushido concept caused by the coming of a new era.